2000
DOI: 10.1095/biolreprod62.3.726
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Oxytocin Release from Microdialyzed Bovine Corpora Lutea During Spontaneous and Prostaglandin-Induced Regression

Abstract: The release of luteal oxytocin during spontaneous and prostaglandin-induced luteolysis was investigated in cows. A continuous-flow microdialysis system was used in 11 cows to collect dialysates of the luteal extracellular space between Days 12 and 24 postestrus. Seven cows were untreated and were expected to exhibit spontaneous luteolysis during sampling, whereas 4 cows received prostaglandin F(2alpha) (PGF(2alpha)) systemically between Days 13 and 15 to induce luteolysis during sampling. Oxytocin was detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
(24 reference statements)
1
5
1
Order By: Relevance
“…That study measured the luteal OXT concentration using unextracted dialysate perfusion, whereas we used an extraction method followed by a 24-fold concentration of samples. Therefore, the discrepancy between our present study and the other study [37] is likely due to the different method of extraction of MDS samples. The present study clearly showed that OXT is actively released even after the onset of spontaneous luteolysis in the cow.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…That study measured the luteal OXT concentration using unextracted dialysate perfusion, whereas we used an extraction method followed by a 24-fold concentration of samples. Therefore, the discrepancy between our present study and the other study [37] is likely due to the different method of extraction of MDS samples. The present study clearly showed that OXT is actively released even after the onset of spontaneous luteolysis in the cow.…”
Section: Discussioncontrasting
confidence: 95%
“…This result is consistent with our recent study in which we detected luteal OXT secretion using the same MDS during PGF 2a -induced luteolysis in the cow [19]. However, a previous study by other researchers using MDS reported that the luteal OXT content began to decline on Day 15 and was undetectable by Day 17 of the estrous cycle in the cow [37]. Moreover, luteal OXT was undetectable within 8 h after PGF 2a -induced luteolysis in the cow [37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the blockade of uterine OT receptors with a specific OT antagonist from Day 15 to Day 22 of the cycle affected neither luteolysis nor the duration of the estrous cycle in heifers [51]. These findings raise serious questions as to whether OT of luteal origin plays a significant role in initiating luteal regression in cattle, as suggested previously [4,6,9,17,50,51]. Therefore, PGF 2␣ secretion by the endometrium during luteolysis in cattle may be regulated not only by OT but also by one or more other factors, including TNF␣ [4,9,10].…”
Section: Discussionmentioning
confidence: 75%
“…Altogether, these findings suggest that the luteal concentration of OT is down-regulated during TNF␣-and NOdependent luteolysis. In fact, the concentrations of OT in the blood [49] and in intact [47] and microdialyzed in vivo CL [17,50] are extremely low at the time of spontaneous luteolysis. Moreover, the blockade of uterine OT receptors with a specific OT antagonist from Day 15 to Day 22 of the cycle affected neither luteolysis nor the duration of the estrous cycle in heifers [51].…”
Section: Discussionmentioning
confidence: 99%